Palynology of San Vincenzo-Stromboli: Interdisciplinary perspective for the diachronic palaeoenvironmental reconstruction of an island of Sicily. (April 2020) - Mercuri, A.M.; Cannavò, V.; Clò, E.; Di Renzoni, A.; Florenzano, A.; Rattighieri, E.; Yoon, D.; Levi, S.T.
Highlights: Pollen testifies landscape transformations in the Stromboli island. Palaeoenvironmental research without plant macroremains preservation. Availability of resources in a limited space from Bronze to Medieval ages. Human pressure has strongly influenced the local landscape since Bronze Age. Current vegetation has its origins in the Medieval period. Abstract: This paper presents the results obtained from palynological research carried out at the archaeological site of San Vincenzo-Stromboli (Aeolian Islands, Sicily) during seven fieldwork seasons (2009–2015). The site has had discontinuous occupation since the Neolithic; the main remains are dated to the Bronze Age, late Roman and late Medieval phases. Pollen analyses were carried out on 60 samples taken from different archaeological contexts, and about 1/3 had enough pollen to calculate pollen spectra. The aim of the research was to gain new data on the economy and productive activity of the island, and to reconstruct the landscape focusing primarily on the Bronze Age, and then on the other occupational phases. An interdisciplinary approach integrating different disciplines has facilitated new interpretations about landscape and human activities. Pollen suggests that oak woodland and Mediterranean evergreen vegetation have been part of the natural plant cover of the area since the first occupation. Early evidence of agrarian practices, including cereal cultivation, dates back to the Bronze Age while the current vegetation seems to have originated during the Medieval period.